2011
DOI: 10.1158/2159-8290.cd-11-0102
|View full text |Cite|
|
Sign up to set email alerts
|

An LXR Agonist Promotes Glioblastoma Cell Death through Inhibition of an EGFR/AKT/SREBP-1/LDLR–Dependent Pathway

Abstract: Glioblastoma (GBM) is the most common malignant primary brain tumor of adults and one of the most lethal of all cancers. EGFR mutations (EGFRvIII) and PI3K hyperactivation are common in GBM, promoting tumor growth and survival, including through SREBP-1-dependent-lipogenesis. The role of cholesterol metabolism in GBM pathogenesis, its association with EGFR/PI3K signaling, and its potential therapeutic targetability are unknown. Here, studies in GBM cell lines, xenograft models and GBM clinical samples, includi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
395
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(431 citation statements)
references
References 62 publications
14
395
1
3
Order By: Relevance
“…15 Many studies have shown that LXR agonists could inhibit cancer cell proliferation by modulating cell cycle protein expression 2,8,9,16 and/or induce cancer cell death, mainly through caspase-3-dependent apoptosis. 5,7 We demonstrate here for the first time that LXR agonist activation of LXRb can induce pyroptotic cell death through an NLRP3 inflammasome-dependent caspase-1 activation pathway. This effect seems to be quite surprising, as many studies report that LXR is mainly a negative regulator of inflammation by downregulating the expression of selective inflammatory genes (e.g., il1b, il6, inos, cox2, mmp9, mcp1, mcp3) through a process that involves DNA interaction, known as transrepression.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…15 Many studies have shown that LXR agonists could inhibit cancer cell proliferation by modulating cell cycle protein expression 2,8,9,16 and/or induce cancer cell death, mainly through caspase-3-dependent apoptosis. 5,7 We demonstrate here for the first time that LXR agonist activation of LXRb can induce pyroptotic cell death through an NLRP3 inflammasome-dependent caspase-1 activation pathway. This effect seems to be quite surprising, as many studies report that LXR is mainly a negative regulator of inflammation by downregulating the expression of selective inflammatory genes (e.g., il1b, il6, inos, cox2, mmp9, mcp1, mcp3) through a process that involves DNA interaction, known as transrepression.…”
Section: Discussionmentioning
confidence: 77%
“…7 Finally, LXRs were shown to be able to decrease colon cancer cell proliferation through inhibition of the oncogenic activity of b-catenin 8 or by modulating the expression of cell cycle regulators. 9 However, a common feature of these reports is that all these mechanisms only involved the transcriptional activity of LXR.…”
mentioning
confidence: 99%
“…In glioblastoma cells overexpressing the EGFR, EGF stimulated PI3K/Akt-driven up-regulation of SREBP1 and LDLR (Guo, Reinitz et al 2011). An LXR agonist induced MYLIP/IDOL-mediated degradation of LDLR, ABCA1-mediated cholesterol efflux, and cell death both in vitro and in an animal model.…”
Section: Experimental and Mechanistic Evidence For Role Of Ldl In Cancermentioning
confidence: 99%
“…Activation of the p42/44 (MAPK) cascade was sufficient to induce LDLR transcription in human hepatoma HepG2 cells expressing oncogenic Raf-1 kinase (Kapoor, Atkins et al 2002). In glioblastoma cells, chronic activation of the EGF receptor tyrosine kinase, or other mechanisms which ultimately activated the PI3K/AKT pathway, led to increased expression of SREBP1 and the LDLR and to LDL-responsive proliferation (Guo, Reinitz et al 2011). …”
Section: Experimental and Mechanistic Evidence For Role Of Ldl In Cancermentioning
confidence: 99%
“…ACC and FAS are overexpressed in numerous types of cancers (2,8) while high levels of mono unsaturated fatty acids (MUFA) were found in tumors (9) as a result of increased SCD1 expression and activity. SREBP1 has also been implicated in tumor growth (10). Therefore, high rate of lipogenesis is probably associated with tumorogenesis.…”
Section: Introductionmentioning
confidence: 99%